2022
DOI: 10.3390/cells11142249
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibition in Acute Myeloid Leukemia and Myelodysplastic Syndromes

Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of many solid tumors, with limited progress made in the area of myeloid malignancies. The low mutational burden of acute myeloid leukemia (AML) is one potential reason behind the lack of activity of T-cell harnessing ICIs, particularly CTLA-4 and PD-1 inhibitors. Innate immune checkpoints play a critical role in the immune escape of AML and myelodysplastic syndromes (MDS). The CD47 targeting agent, magrolimab, has shown promising activity wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…90,92,[103][104][105][106] For myeloid malignancies, however, such immune networks have been only minimally evaluated (for example, in the pediatric AML setting 107 ) in part due to the technical obstacles of applying high dimensional sequencing and spatial profiling approaches to marrow tissue that has been conventionally processed using harsh decalcification procedures, though advancing technologies and analytical methods may overcome this challenge. [108][109][110] The response of AML to immunotherapies such as ICB have been disappointing, 65,111 and defining the role of TLS-like structures or other cellular networks could serve to advance our understanding of the critical cellular players needed to coordinate an effective anti-leukemia response. Indeed, in our study, through integrated single cell analysis of marrow biospecimens collected from a deeply clinically annotated cohort of AML immune therapy responders and nonresponders, with incorporation of timeresolved prediction of cell-cell interactions, protein level validations in independent patients, and functional analysis, we gained numerous insights into the relationships between the immunologically diverse BME and response to the archetypal adoptive cellular therapy, DLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90,92,[103][104][105][106] For myeloid malignancies, however, such immune networks have been only minimally evaluated (for example, in the pediatric AML setting 107 ) in part due to the technical obstacles of applying high dimensional sequencing and spatial profiling approaches to marrow tissue that has been conventionally processed using harsh decalcification procedures, though advancing technologies and analytical methods may overcome this challenge. [108][109][110] The response of AML to immunotherapies such as ICB have been disappointing, 65,111 and defining the role of TLS-like structures or other cellular networks could serve to advance our understanding of the critical cellular players needed to coordinate an effective anti-leukemia response. Indeed, in our study, through integrated single cell analysis of marrow biospecimens collected from a deeply clinically annotated cohort of AML immune therapy responders and nonresponders, with incorporation of timeresolved prediction of cell-cell interactions, protein level validations in independent patients, and functional analysis, we gained numerous insights into the relationships between the immunologically diverse BME and response to the archetypal adoptive cellular therapy, DLI.…”
Section: Discussionmentioning
confidence: 99%
“…The CD226-TIGIT-PVR/NECTIN axis is a well-established immune checkpoint pathway responsible for fine-tuning T cell activation or exhaustion. 80,83,131,132 Possibly, given the relative resistance of AML to conventional ICB, 65,111,[133][134][135]111 TIGIT may be a fruitful target for ICB in a subset of AML patients, although definitive experiments are needed to identify the specific patients who may benefit from such a strategy and to further elucidate possible mechanisms of response or resistance. Third, the intrinsic anti-leukemia activity of CD8+ ZNF683 Hi CTLs make them a highly attractive candidate for cellular therapy for AML.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of characteristics between overall responders and non-responders showed that non-responders tended to have more TP53 mutations and more secondary and therapy-related AML. Notably, there was no difference in the OS between responders who continued on therapy beyond remission and those bridged to allo-SCT, suggesting the potential ability of nivolumab to restore anti-tumor immune surveillance and eradicate MRD [68]. Based on this, a pilot Phase II clinical trial studying the efficacy and safety of nivolumab as maintenance therapy in AML was conducted in patients with high-risk AML in remission not being considered for allogeneic HSCT.…”
Section: Immune Checkpoint Inhibitionmentioning
confidence: 99%
“…Immune escape is primarily attributed to the downregulation of immune cell function and exhaustion. It includes the upregulation of immune checkpoint (IC) receptors and a high expression of IC ligands on tumor cells ( 8 ). Our previous work demonstrated that T-cell immune inhibitory receptors, such as program death-1 (PD-1), T-cell immunoreceptor with immunoglobulin and ITIM domain (TIGIT), T-cell immunoglobulin mucin 3 (Tim-3), and T lymphocyte activation gene-3 (LAG-3), show increased expression in T cells from patients with newly diagnosed AML (AMLy-DN) and those with relapsed AML.…”
Section: Introductionmentioning
confidence: 99%